2017
DOI: 10.4236/oalib.1103813
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Is Correlated with Severity of Allergic Rhinitis

Abstract: Background: Vitamin D deficiency has been targeted as a cause of the increased incidence of allergic rhinitis. Many factors, including sun exposure, influence vitamin D levels. Indonesia is a country with abundant sunshine exposure throughout the year; therefore, Indonesian residents are not expected to have inadequate vitamin D levels. Objective: This study aimed to investigate whether vitamin D deficiency levels are correlated with disease spectrum among allergic rhinitis patients. Material and Method: A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…One reason that may be related to data on low levels of Vitamin D in research subjects is the prevalence of Vitamin D deficiency which is indeed low in Asian or Indonesian populations in particular, as the study from Sari et al in 2017 showed Vitamin D levels of 292 women in North Sumatra, as many as 122 (41.7%) subjects showed a deficient level of Vitamin D, and 158 (54.1%) subjects showed an insufficient level of Vitamin D [22]. The study from Sudiro et al in 2017 showed that from 76 subjects, which consisted of 46 subjects with allergic rhinitis and 30 healthy subjects at the ear, nose and throat (ENT) Polyclinic, Dr. Hasan Sadikin Hospital, Bandung, West Java, as many as 73 (96%) subjects showed a deficient level of Vitamin D. Two (2.6%) subjects showed an insufficient level of Vitamin D [23 ]. In the study from Judistiani et al in 2019, it was shown that of 203 pregnant women at the Gynecology Polyclinic, Dr. Hasan Sadikin Hospital, Bandung, West Java, also suffered from deficient levels of vitamin D at a rate as high as 75% [24].…”
Section: Discussionmentioning
confidence: 99%
“…One reason that may be related to data on low levels of Vitamin D in research subjects is the prevalence of Vitamin D deficiency which is indeed low in Asian or Indonesian populations in particular, as the study from Sari et al in 2017 showed Vitamin D levels of 292 women in North Sumatra, as many as 122 (41.7%) subjects showed a deficient level of Vitamin D, and 158 (54.1%) subjects showed an insufficient level of Vitamin D [22]. The study from Sudiro et al in 2017 showed that from 76 subjects, which consisted of 46 subjects with allergic rhinitis and 30 healthy subjects at the ear, nose and throat (ENT) Polyclinic, Dr. Hasan Sadikin Hospital, Bandung, West Java, as many as 73 (96%) subjects showed a deficient level of Vitamin D. Two (2.6%) subjects showed an insufficient level of Vitamin D [23 ]. In the study from Judistiani et al in 2019, it was shown that of 203 pregnant women at the Gynecology Polyclinic, Dr. Hasan Sadikin Hospital, Bandung, West Java, also suffered from deficient levels of vitamin D at a rate as high as 75% [24].…”
Section: Discussionmentioning
confidence: 99%
“…1 In a study conducted by Sudiro, dust mites were also the highest allergen. 15 The ARIA-WHO classification is the current classification of AR used. The classification was made by WHO because the conventional classification that divides AR based on the time of allergen exposure into chronic, seasonal, and occupational AR is not suitable for the patient's clinical symptom status.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study is similar to research conducted by Basyir and Sudiro at Dr. Hasan Sadikin General Hospital Bandung which stated that the most frequent classification was moderate-severe persistent. 15,16 Most of the patients who present to the physician have had moderatesevere AR disease for more than 4 days per week and more than 4 weeks. 17 The existence of geographical variations around the world can cause a difference in the distribution of aeroallergens, such as dust mites, in different regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in allergic diseases, vitamin D acts on the human immune system through inhibitory functions on the growth cycle of human dendritic cells and the functions of T cells, stimulating the secretion of specific cytokines such as IL-10 [ 47 , 48 ]. It has been widely discussed how patients diagnosed with allergic disease are characterized by below normal levels of vitamin D and how this hormonal deficiency leads to a greater severity of symptoms [ 49 , 50 , 51 ]. In fact, the metabolite of vitamin D 1,25 (OH) 2VD3 can act by inhibiting T-helper 1 (TH1) and stimulating the responses of TH2 cells.…”
Section: Immunological Correlation Between Vd3 and Crswnp/crssnpmentioning
confidence: 99%